Antiproliferative, antioxidant and anti-inflammatory effects of Boswellia Sacra on human pancreatic cancer cells - Becer, Eda; Altundag, Erguel Mutlu; Ozbilenler, Cahit; Vatansever, Hafize Seda; Baser, Kemal Huesnue Can (Taylor & Francis Ltd, 2023)
Pancreatic cancer is a highly lethal and malignant tumor with high occurrence worldwide. Natural products such as essential oils with a lack of side effects may benefit pancreatic cancer supplementary therapy. Essential oil of BS was prepared by distillation of the gum resin and also has been shown to have anti-cancer and antioxidant activities. The present study aimed to determine the anti-cancer, antioxidant and anti-inflammatory activities in PANC-1 cells. Chemical Functional Moieties of Boswellia sacra essential oil were determined by Fourier transform infrared (FTIR) spectroscopy. The essential oil was simultaneously analyzed by GC/MS and GC-FID. Cell viability was determined by MTT assay. Anti-cancer activity of BS essential oil was investigated by immunocytochemistry using antibodies against STAT-3, IHH, beta-catenin, CD133, and Ki-67. The antioxidant activity of BS essential oil was tested by DPPH method. 41 compounds were identified in the essential oil. The IC50 value of BS essential oil was found as 130 mu g/mL in PANC-1 cells. Ki-67 immunoreactivity significantly decreased in BS essential oil-treated PANC-1 cells. STAT-3 and beta-catenin immunoreactivities significantly increased in BS essential oil-treated PANC-1 cells. Also, BS essential oil showed antioxidant and anti-inflammatory activities. We conclude that BS essential oil may suppress proliferation via the beta-catenin activation pathway in PANC-1 cells.
Keywords: Boswellia sacra (BS); Anti-proliferative; Anti-cancer; Anti-inflammatory; PANC-1 cells